Management of Graduate Quality Improvement in Vocational High Schools - Abubakar Abubakar; Muhammad Yusuf; Siraj Siraj; Syamsul Bahri (LPPM Universitas Malikussaleh, 2024)
The quality of Vocational High Schools graduates often depends on several factors, such as the alignment of the curriculum with industry standards, the quality of teaching, the practical experience provided to students, and the involvement of industry partners. This study aims to the analyze the management of improving graduate quality in Vocational High Schools and identify the factors that affect the improvement of Vocational High Schools graduate quality. Through this research, it is hoped that appropriate solutions will be found to improve the quality of SMK graduates, enabling them to be more prepared to face the workforce and contribute to economic development and the advancement of industry in the future. This research uses a qualitative approach with a case study method. Data analysis follows the Miles & Huberman model, which consists of data collection, data presentation, data reduction, and conclusion. This research identifies several challenges faced by Vocational High Schools in improving the quality of their graduates. The curriculum's mismatch with industry needs, lack of collaboration with the industrial sector, the need to enhance teacher competence, and ineffective management are some of the factors hindering the improvement of SMK graduate quality